Birth Weight and the Risk of Cardiovascular Outcomes: A Report From the Large Population-Based UK Biobank Cohort Study - Huang, Xin; Liu, Jun; Qi, Lu; Adachi, Jonathan D.; Wu, Jing; Li, Ziyi; Meng, Qiong; Li, Guowei; Lip, Gregory Y. H. (Frontiers in Cardiovascular Medicine, 2022)
Background: Birth weight has been reported to be associated with the risk of incident cardiovascular disease (CVD); however, the relationship remains inconclusive. Here, we aimed to prospectively assess the associations between birth weight and CVD risk using the data from UK Biobank, a large-scale, prospective cohort study. Methods: We included 270,297 participants who were free of CVD at baseline and reported their birth weight for analyses. The primary outcome was incident CVD. Hazard ratios (HRs) and 95% confidence intervals (CIs) for outcomes were calculated using Cox proportional hazards models adjusted for potential confounding variables. Results: During a median follow-up of 8.07 years (IQR: 7.4–8.7 years), 10,719 incident CVD events were recorded. The HRs for low birth weight versus normal birth weight (2.5–4.0 kg) were 1.23 (95% CI: 1.09 to 1.38) for risk of incident CVD, 1.52 (95% CI: 1.18 to 1.95) for stroke, 1.33 (95% CI: 1.07 to 1.64) for myocardial infarction, and 1.15 (95% CI: 1.01 to 1.32) for CHD. For the ones with low birth weight, the risk of CVD is reduced by 11% for every kilogram of birth weight gain. The association of low birth weight with CVD was stronger among those younger than 55 years (p = 0.001). No association between high birth weight and risk of cardiovascular outcomes was found. Conclusions: Low birth weight was associated with an increased risk of cardiovascular events. These findings highlight the longstanding consequence of low birth weight on cardiovascular system.